Progression of Heart Failure in People with Type 2 Diabetes in Germany: An Analysis Using German Health Insurance Claims Data - Keni Cheng-Siang Lee; Tobias Wagner; Adee Kennedy; Michael Wilke (Journal of Health Economics and Outcomes Research)
# Background Individuals with type 2 diabetes (T2D) show high risk of heart failure (HF). Left ventricular ejection fraction is a major factor for disease progression. In Germany, no recent longitudinal data are available.